Educação e prevenção em Saúde Bucal traduzidas em libras - Dias, Soniamar Faria Queiroz (2018)
The social, cultural, religious differences, ethnic, gender, diversity and human culture, are constantly changing and has been an essential condition for the understanding and the understanding of the unique characteristics of human societies; the language is an expression of culture, an element indicator of linguistic expressions of a particular population. The purpose of this study was to elaborate an oral health education and prevention material translated into the Brazilian Sign Language (Libras), which is the first language of the Brazilian deaf community, according to Decree No. 5,626, dated December 20, 2005, which regulated and recognized the right of a bilingual education for deaf Brazilian people. Thus, for the development of this study, three videos were developed with guidelines on oral health. They were translated into Brazilian Language of Signals - Pounds and were evaluated by four interpreters of Libras. After this procedure the videos were watched and evaluated by 19 deaf people who answered a questionnaire about the quality and comprehension of the presented material and presented suggestions about it. In addition, the material was made available on https://www.youtube.com/watch?v=Q3BPb90Rhjg social media – Youtube in order to socialize your content. After evaluating the results, it was concluded that, for most of the participants, the material was considered optimal in all queried questions with suggestions for the expansion and dissemination of the same to the deaf communities.